Immune cell dynamics and the impact on the efficiency of transvascular antitumor interventional therapies in hepatocellular carcinoma patients - Sun, Yuan-Dong; Zhang, Hao; Li, Yuan-Min; Zhou, Chun-Xiao; Han, Jian-Jun (Frontiers in Immunology, 2024)
Declaration of generative AI and AI-assisted technologies in the writing process: This is to declare that all results and analyses presented in our paper were conducted solely by the authors, without the intervention of Artificial Intelligence (AI) or related technologies. We affirm that the data processing, interpretation, and conclusions drawn in this study were executed manually by the research team, ensuring that the insights and findings reflect our understanding and expertise in the subject matter. We did not employ AI tools or algorithms for data analysis or result generation, thus maintaining the integrity and authenticity of the research. During the preparation of this work the authors used ChatGPT in order to improve language and readability. The authors reviewed and edited the content and took full responsibility for the content of the publication. Highlights 1.Higher WBC, lymphocyte, monocyte, and basophil counts correlate with successful HCC treatment outcomes. 2.T cell abnormalities associate with clinical factors like BMI, diabetes, infection, and multiple lesions. 3.Total T cell abnormalities link with age, BMI, hypertension, and AFP levels in HCC patients. 4.Certain immune cell abnormalities do not significantly influence progression-free survival in HCC. 5.Personalized treatment strategies enhance efficacy by considering immune cell dynamics and patient-specific factors.